Assessment of agreement between invasive and non-invasive blood pressure measurements in critically ill patients - Ninziza, Jadot (My University, 2010)
The purpose of the study was to describe and compare the limits of agreement between invasive blood pressure (IBP) and non-invasive blood pressure (NIBP) readings obtained on patients in the adult critical care units (CCU) of a tertiary health care institution, to describe the factors that affect accuracy of both techniques, to describe the difference in terms of accuracy and sensitivity and the reasons given by the clinical practitioners for their choice of blood pressure measurement technique. A non-experimental descriptive comparative, prospective design was utilized in this two part study. The sample comprised of CCU patients (n = 80) in five adult critical care units over a 3-month period. Non-probability purposive sampling was utilized to obtain the desired sample in part one of the study. Data collection was via IBP and NIBP measurements obtained by the researcher and a record review of the patient’s critical care charts. Part two of the study comprised of clinical practitioners (n=50) and convenience sampling method was utilized. Descriptive and inferential statistics were used to analyse data. At the 95% confidence interval, the limits of agreements were found to be in range of ± 35 mmhg of IBP and NIBP systolic, ± 19.5 mmHg of IBP and NIBP diastolic and ±19.3 mmhg IBP and NIBP of mean arterial pressure. In practical terms this means that IBP and NIBP can not be used interchangeably in CCUs as the two methods did not consistently provide similar measurements because there was a high level of disagreement that included clinically important discrepancy of more than 10 mmhg which is the cut off acceptable reference in terms of discrepancy between the two BP techniques and add to the growing literature suggesting that IBP remains the gold standard technique for measuring the blood pressure in critical care setting. Factors such as Inotropic/ vasopressor support, sedation / analgesia, mechanical ventilation and severity of illness (APACHE II score) did not show significant influence on the discrepancy of the two BP techniques. In the second part of the study, more than 80 % of the sample of clinical practitioners acknowledged that the IBP technique remains the gold standard.
MSc (Nursing), Faculty of Health Sciences, University of the Witwatersrand
Keywords: blood pressure measurement technique; ICU patients